Conflicting actions of 4-vinylcatechol in rat lymphocytes under oxidative stress induced by hydrogen peroxide. (3rd July 2020) - Kishida, Takumi; Funakoshi, Yurie; Fukuyama, Yuya; Honda, Sari; Masuda, Toshiya; Oyama, Yasuo
Abstract: 4-Vinylcatechol (4VC) has been identified as an aroma compound in roasted foods, especially coffee. It is also a component in traditional herbal medicines. This compound may be subconsciously ingested through foods and herbs. Recent experimental evidence has shown that 4VC possesses an antioxidative action. However, the antioxidative action of 4VC at cellular levels is not well characterized. The effects of 4VC (0.1–100 µM) were examined on rat thymic lymphocytes without and with oxidative stress induced by 300 µM hydrogen peroxide (H2 O2 ). Cell treatment with 100 µM 4VC alone for 4 h significantly increased the population of dead cells. Thus, 4VC at 100 µM or above elicits cytotoxicity. However, 4VC at sublethal concentrations (1–10 µM) significantly attenuated the H2 O2 -induced increase in cell lethality in a concentration-dependent manner. While application of 10 µM 4VC slowed the process of cell death induced by H2 O2, 4VC did not antagonize the H2 O2 -induced reduction of cellular nonprotein thiols. Although 4VC at 10 µM did not affect intracellular Ca 2+ and Zn 2+ levels, the agent potentiated the H2 O2 -induced increases in these levels. These actions of 10 µM 4VC are adverse to the cells under the oxidative stress. However, 10 µM 4VC partly attenuated the cell death induced by 100 nM A23187, a calcium ionophore. There are conflicting actions of 4VC at 1–100 µM on the cells under oxidative stress although the agent is used for an antioxidant. Thus, caution is required when using 4VC as a therapeutic agent.